Hungarian Monitoring, 21 March 1988 . [Magyar rádiófigyelő], 1988. március 21 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Shevardnadze in Washington - Armenian-Azeri national minority disputes - Czechoslovak-Romanian heads of state in talks Domestic Affairs: - Károly Grósz in talks with heads of higher education institutions - Pozsgay's speech on parliamentarism, extension of the public sphere - 69th anniversary of the declaration of the Republic of Councils - Activities of the Central Physics Research Institute at risk - Exhibition opens in Budapest of American designers' work - Working without permits in the FRG Külpolitika: - Sevardnadze Washingtonban - Örmény-azeri nemzetiségi viták - Csehszlovák - Román kormányfői tárgyalások Belpolitika: - Grósz Károly felsőoktatási intézmények vezetőivel tárgyalt - Pozsgay beszéd a parlamentarizmusról, a nyilvánosság kiterjesztéséről - A Tanácsköztársaság kikiáltásának 69. évfordulója - Veszélyben a Központi Fizikai Kutatóintézet tevékenysége - Amerikai formatervezők munkáiból nyílt kiállítás Budapesten - Engedély nélküli munkavállalás az NSZK-ban